Réponses

Meilleure réponse !
2013-06-20T17:59:25+02:00

Bonjour,

 

Dans chaque cas, il faut remplacer x par sa valeur, puis calculer.

Ainsi :

g\left(x\right) = 2x^2-3x\\ \\ g\left(-2\right) = \left(-2\right)^2-3\times \left(-2\right)\\ g\left(-2\right) = 2\times 4+6 = 8+6 = 14\\ \\ g\left(0\right) = 2\times 0^2-3\times 0\\ g\left(0\right) = 2\times 0-0\\ g\left(0\right) = 0\\ \\

g\left(\frac 12\right) = 2\times \left(\frac 12\right)^2-3\times \frac 12\\ g\left(\frac 12\right) = 2\times \frac 14 -\frac 32\\ g\left(\frac 12\right) = \frac 12 -\frac 32\\ g\left(\frac 12\right) = -1\\ \\ g\left(10^3\right) = 2\times \left(10^3\right)^2-3\times 10^3\\ g\left(10^3\right) = 2\times 10^{3 \times 2}-3\times 10^3\\ g\left(10^3\right) = 2\times 10^6 - 3\times 10^3\\ g\left(10^3\right) = 2000000 - 3000 = 1997000